The Burden and Clinical Presentation of Pulmonary Tuberculosis in Adults With Severe Respiratory Illness in a High Human Immunodeficiency Virus Prevalence Setting, 2012–2014. (7th August 2017) - Walaza, Sibongile; Tempia, Stefano; Dreyer, Andries; Dawood, Halima; Variava, Ebrahim; Martinson, Neil A.; Moyes, Jocelyn; Cohen, Adam L.; Wolter, Nicole; von Mollendorf, Claire; von Gottberg, Anne; Haffejee, Sumayya; et al.
Abstract: Background: Understanding the burden and clinical presentation of tuberculosis in patients with severe respiratory illness (SRI) has important implications for anticipating treatment requirements. Methods: Hospitalized patients aged ≥15 years with SRI at 2 public teaching hospitals in periurban areas in 2 provinces (Edendale Hospital in Pietermaritzburg, KwaZulu-Natal Province and Tshepong Hospital in Klerksdorp, North West Province) were enrolled prospectively from 2012 to 2014. Tuberculosis testing included smear microscopy, culture, or Xpert MTB/Rif. Results: We enrolled 2486 individuals with SRI. Of these, 2097 (84%) were tested for tuberculosis, 593 (28%) were positive. Tuberculosis detection rate was 18% (133 of 729) in individuals with acute (≤14 days) presentation and 34% (460 of 1368) in those with chronic (>14 days) presentation. Among laboratory-confirmed tuberculosis cases, those with acute presentation were less likely to present with cough (88% [117 of 133] vs 97% [447 of 460]; ajusted odds ratio [aOR] = 0.2, 95% confidence interval [CI] = 0.1–0.5), night sweats (57% [75 of 132] vs 73% [337 of 459]; aOR = 0.4, 95% CI = 0.3–0.7), or be started on tuberculosis treatment on admission (63% [78 of 124] vs 81% [344 of 423]; aOR = 0.4, 95% CI = 0.3–0.7), but they were more likely to be coinfected with pneumococcus (13% [16 of 124] vs 6% [26 of 411]; aOR 2.3, 95% CI 1.3–5.3) than patients with chronic presentation. Annual incidence of acute and chronic tuberculosis-associated SRI per 100000 population was 28 (95% CI = 22–39) and 116 (95% CI = 104–128), respectively. Conclusions: In this setting, tuberculosis, including acute presentation, is common in patients hospitalized with SRI.